Сучасні тенденції та чинники міграційного руху населення у Київській області - Драгунова, Т.А.; Майданік, І.П. (Інститут демографії та соціальних досліджень НАН України, 2009)
В статье рассматриваются особенности миграционных процессов населения Киевской области. Внимание сосредоточено на выявлении факторов, влияющих на формирование миграционных потоков, их интенсивность и направленность, а также на изучении факторов, которые определяют миграционную ситуацию в административных районах Киевской области. In the article features of migratory processes of the population of the Kiev region are considered. The attention is concentrated to revealing of factors influencing migratory flows formation, their intensity and destination, and also on studying of factors which define a migratory situation in administrative areas of the Kiev region.